Genome-wide CRISPR screening reveals genes essential for cell viability and resistance to abiotic and biotic stresses in Bombyx mori - Chang, Jiasong; Wang, Ruolin; Yu, Kai; Zhang, Tong; Chen, Xiaoxu; Liu, Yue; Shi, Run; Wang, Xiaogang; Xia, Qingyou; Ma, Sanyuan

(untitled) (Genome Research, 2020)
High-throughput genetic screens are powerful methods to interrogate gene function on a genome-wide scale and identify genes responsible to certain stresses. Here, we developed a piggyBac strategy to deliver pooled sgRNA libraries stably into cell lines. We used this strategy to conduct a screen based on genome-wide clustered regularly interspaced short palindromic repeat technology (CRISPR)-Cas9 in Bombyx mori cells. We first constructed a single guide RNA (sgRNA) library containing 94,000 sgRNAs, which targeted 16,571 protein-coding genes. We then generated knockout collections in BmE cells using the piggyBac transposon. We identified 1006 genes that are essential for cell viability under normal growth conditions. Of the identified genes, 82.4% (829 genes) were homologous to essential genes in seven animal species. We also identified 838 genes whose loss facilitated cell growth. Next, we performed context-specific positive screens for resistance to biotic or nonbiotic stresses using temperature and baculovirus separately, which identified several key genes and pathways from each screen. Collectively, our results provide a novel and versatile platform for functional annotations of B. mori genomes and deciphering key genes responsible for various conditions. This study also shows the effectiveness, practicality, and convenience of genome-wide CRISPR screens in nonmodel organisms.